Application of the hypervirial theorem scheme to the potential -D/cosh^2(r/R) - Liolios, T.; Grypeos, M. (HNPS Advances in Nuclear Physics, 2020)
The well known potential -D/cosh^2(r/R)is studied with the aim of obtaining approximate analytic expressions mainly for the energies of the excited states with l≠0. Use is made of the Hypervirial Theorems (HVT) in conjunction with the Hellmann-Feynman Theorem (HFT) which provide a very powerful scheme especially for the treatment of 'Oscillator-like' potentials,as previous studies have shown. The energy eigenvalues are calculated in the form of an expansion, the first terms of which, in many cases, yield very satisfactory results.